دور النوادي الطلابية في التنشيط الاعلامي داخل الجامعة - حشاشنة عائشة; بوعزة أمال; د/بوسعيد رندة (جامعة عمار ثليجي- الاغواط, 2025)
ملخص باللغة العربية : تهدف هذه الدراسة إلى الكشف عن دور النوادي الطلابية في التنشيط الإعلامي داخل الجامعة، من خلال دراسة ميدانية حول نادي العلوم بجامعة الأغواط، حيث شملت العينة 140 طالبًا وطالبة من مختلف التخصصات. تم اعتماد المنهج الوصفي التحليلي، مع الاستعانة بأداة الاستبيان لجمع البيانات وتحليلها . أظهرت النتائج أن نادي العلوم يحظى باهتمام معتبر لدى الطلبة، إذ يرى 67.86 % منهم أنه يُعتبر وسيلة فعالة أو فعالة نسبيًا لاكتشاف المواهب الإعلامية وتطويرها، كما أن 35.71 % من المستجوبين يتابعون محتواه نظرًا لجودته العلمية، مقابل 28.57 % ينجذبون لأسلوبه الإعلامي الجذاب. ومع ذلك، كشفت النتائج عن ضعف نسبي في التفاعل مع المحتوى، حيث يقر 39.29 % أنهم يتفاعلون نادرًا، و 21.43 % لا يتفاعلون إطلاقًا، وهو ما يشير إلى ضرورة تطوير آليات النشر والتفاعل . كما أبرزت الدراسة أن الإعلام الطلابي يلعب دورًا إيجابيًا في تعزيز المشاركة الجامعية، حيث أفاد 82.14 % من المشاركين بأن الخطاب الإعلامي للنادي يترك أثرًا إيجابيًا أو محايدًا إيجابيًا لديهم. وقد اقترح الطلبة جملة من التوصيات، أبرزها: توفير دعم لوجستي وتقني، وتمويل الورش والمعدات، ما يدل على وعيهم بأهمية تطوير الإعلام الجامعي . خلصت الدراسة إلى أن نادي العلوم يُعد فاعلًا إعلاميًا محوريًا داخل الجامعة، ويستدعي ذلك دعمًا مؤسساتيًا شاملًا يدمج بين التكوين، والتمويل، والمرافقة الإدارية لضمان ديمومة الأداء وفعاليته . كلمات مفتاحية : الإعلام الجامعي، النوادي الطلابية، نادي العلوم، التفاعل الطلابي . Abstract: This study aims to explore the role of student clubs in activating university media, through a field study on the Science Club at Laghouat University. The study surveyed a sample of 140 students from various academic fields using a descriptive-analytical method supported by a structured questionnaire. The results indicate that the Science Club holds a significant place among students. About 67.86% consider it an effective or relatively effective platform for discovering and developing media talents. Furthermore, 35.71% follow the club due to the scientific quality of its content, while 28.57% are drawn to its attractive media style. However, the study also noted a relatively weak level of interaction with published content, with 39.29% reporting rare engagement and 21.43% no engagement at all. This highlights the need for improving publishing strategies and audience engagement. The findings also confirm the positive impact of student media on university participation. A large portion of the respondents (82.14%) acknowledged that the club’s media discourse has a very positive or somewhat positive effect. Students also proposed several recommendations, notably providing logistical and technical support, and funding workshops and equipment, reflecting their awareness of the importance of enhancing university media. In conclusion, the Science Club plays a vital role in university media activities, and its development requires an institutional strategy that combines training, funding, and administrative support to ensure sustained effectiveness. Keywords: university media; student clubs; science club; student engagement